Listening to Community: Towards Best Research Practices in Pond Inlet, Nunavut ... - Spiers, Kent Gordon (Graduate Studies, 2024)
What are the specific conditions and circumstances that can either prevent or facilitate an ethical, meaningful, productive, and respectful collaboration between Settler researchers and Indigenous People engaged in community or regional monitoring programs? How can I bring Settler research and Indigenous knowledge systems together to facilitate more equitable and proactive environmental monitoring programs? My research examines the connections between community-based environmental monitoring, research ethics, and the role of social science in climate change adaptation programs. In this dissertation, I examine the context, community concerns and recommendations for research that emerged during my fieldwork, interviews, and workshops conducted in Pond Inlet and Cambridge Bay, Nunavut, and Calgary, Alberta. It is widely recognized that over the last few decades, the planet has been undergoing rapid climate change, particularly in the Arctic. Climate change has led to a discussion about the role of Settler ...